2016
DOI: 10.3847/0004-637x/825/2/100
|View full text |Cite
|
Sign up to set email alerts
|

Average Spatial Distribution of Cosmic Rays Behind the Interplanetary Shock—global Muon Detector Network Observations

Abstract: We analyze the galactic cosmic ray (GCR) density and its spatial gradient in Forbush Decreases (FDs) observed with the Global Muon Detector Network (GMDN) and neutron monitors (NMs). By superposing the GCR density and density gradient observed in FDs following 45 interplanetary shocks (IP-shocks), each associated with an identified eruption on the sun, we infer the average spatial distribution of GCRs behind IP-shocks. We find two distinct modulations of GCR density in FDs, one in the magnetic sheath and the o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Therefore, the diffusion approach should be valid to explain FR associated FDs detected in a variety of instruments corresponding to different mean energies: muon telescopes at ∼ 50 GV (e.g. Kozai et al 2016), neutron monitors at ∼ 10 GV (e.g. Clem and Dorman 2000), and spacecraft such as the Electron Proton Helium Instrument (EPHIN, Müller-Mellin et al 1995) onboard Solar and Heliospheric Observatory (SOHO, Domingo et al 1995) at ∼ 1 GV (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the diffusion approach should be valid to explain FR associated FDs detected in a variety of instruments corresponding to different mean energies: muon telescopes at ∼ 50 GV (e.g. Kozai et al 2016), neutron monitors at ∼ 10 GV (e.g. Clem and Dorman 2000), and spacecraft such as the Electron Proton Helium Instrument (EPHIN, Müller-Mellin et al 1995) onboard Solar and Heliospheric Observatory (SOHO, Domingo et al 1995) at ∼ 1 GV (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As these shocks propagate, they sweep out galactic cosmic rays forming a depleted region behind them. Kozai et al (2016) studied the cosmic ray density and gradient derived by GMDN observations during Forbush decreases of a number of CME-ICME shock events, originating in several positions at the solar disk. These authors found a distinct modulation of galactic cosmic rays, one related to the shock-sheath region and another due to the ICME flux rope.…”
Section: Modulationmentioning
confidence: 99%
“…A previous study related the cosmic ray decreases associated with shocks were already performed using observations from the GMDN up to 2014 (see, e.g., [13]) and the events were selected using the geomagnetic storm sudden commencement (SSC) listed by the German Research Centre for Geosciences (GFZ) as the identification of the shock arrival at Earth. Although the SSCs are considered to be caused by the interplanetary shocks [14], cosmic rays are not directly modulated by the geomagnetic field conditions but primary by the conditions in the interplanetary magnetic…”
Section: Observation and Data Analysismentioning
confidence: 99%